Fabrication of 0-3 non-lead based piezoceramic/polymer composites using suction technique - T. Sareein (2018)
In this research, 0-3 composites between non-lead based piezoceramic and polymer were fabricated using the suction technique. Bismuth sodium titanate (Bi0.5Na0.5TiO3BNT) which prepared from conventional mixed oxide method was used as active phase whereas epoxy resin was used as matrix phase. The 50% volumetric fraction of BNT/epoxy resin can obtain from suction technique. The physical and piezoelectric properties of composites samples were examined. It can be found that density of composite samples were about 1.78 g/cm3. Moreover, the piezoelectric coefficient (d 33) of sample was 13 pC/N. Furthermore, the microstructure of composites was determined using SEM technique. © 2008 Trans Tech Publications, Switzerland.